2011
DOI: 10.1002/hep.24018
|View full text |Cite
|
Sign up to set email alerts
|

Enteric dysbiosis associated with a mouse model of alcoholic liver disease

Abstract: The translocation of bacteria and bacterial products into the circulation contributes to alcoholic liver disease. Intestinal bacterial overgrowth is common in patients with alcoholic liver disease. The aims of our study were to investigate bacterial translocation, changes in the enteric microbiome, and its regulation by mucosal antimicrobial proteins in alcoholic liver disease. We used a mouse model of continuous intragastric feeding of alcohol or an isocaloric diet. Bacterial translocation occurred prior to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
680
5
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 694 publications
(772 citation statements)
references
References 82 publications
45
680
5
12
Order By: Relevance
“…Preclinical studies have shown that chronic ethanol administration induces in rats a dysbiosis (45), and in mice a decrease in the level of Ruminococcaceae (46), or a decrease in the level of Firmicutes and an increase in Bacteroidetes (47). In humans, few studies have evaluated the gut microbiome of AD subjects and never in relation to gut permeability.…”
Section: Effect Of Alcohol Withdrawal On Gut-microbiota Compositionmentioning
confidence: 99%
“…Preclinical studies have shown that chronic ethanol administration induces in rats a dysbiosis (45), and in mice a decrease in the level of Ruminococcaceae (46), or a decrease in the level of Firmicutes and an increase in Bacteroidetes (47). In humans, few studies have evaluated the gut microbiome of AD subjects and never in relation to gut permeability.…”
Section: Effect Of Alcohol Withdrawal On Gut-microbiota Compositionmentioning
confidence: 99%
“…Recent data show that OPN binds lipopolysaccharide (LPS) and protects against early alcohol-induced liver injury by blocking the TNF-α effects in the liver [137] . Furthermore, OPN is reported to be a downstream effector of the Hedgehog pathway, which modulates fibrosis and is involved in peculiar aspects of hepatic carcinogenesis [138] .…”
Section: Mechanism Of Alcohol-induced Fibrogenesismentioning
confidence: 99%
“…Multiple studies in animal models of NAFLD and ALD have shown a clear association between disease and dysbiosis (44,45). Additionally, there is evidence that the microbiome influences progression of NAFLD, ALD, and viral hepatitis to end-stage liver disease in humans (46,47), highlighting dysbiosis as a possible common denominator in these diseases.…”
Section: Gut Dysbiosismentioning
confidence: 99%